Menentukan Harga Jual Mobil Bekas Menggunakan Fuzzy Logic Metode Sugeno - Ekawati, Nia; Salamena, Alvin Piterson (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
Automotive companies are currently quite common in every country, one of which is Japan. Following this technology, Indonesia has begun to develop automotive production with the city car concept. The car produced in Indonesia is named Agya which is taken from the Sanskrit word which means